2021
DOI: 10.1136/bmjdrc-2021-002553
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and morphology of lipohypertrophic lesions in adults with type 1 diabetes with ultrasound screening: an exploratory observational study

Abstract: IntroductionLipohypertrophy is a common complication of exposure to insulin therapy. Despite the prevalence of lipohypertrophy and its potentially hazardous effects on glucose regulation, it remains a relatively understudied problem in diabetes. The objective of this study was to characterize lipohypertrophic tissue using ultrasound in adults with type 1 diabetes.Research design and methodsAn observational study of 74 people with type 1 diabetes from a diabetes center in South East London. Participants’ insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…38 To determine the severity of each LH area, a severity indicator based on the size and the number of nodules to produce a parameter on potential severity, as shown in Figure 5, has been described. 37 Increasing severity, as indicated by this model, is associated with increasing size and number of LH nodules and increasing amounts of inflammation, thickening, and loss of differentiation between the dermis and SC tissue. The insulin antibody load was also examined in individuals with varying severity of LH, and the antibody titer was associated with the severity of LH as defined in the model.…”
Section: Ultrasound Imaging Of Lipohypertrophymentioning
confidence: 76%
See 3 more Smart Citations
“…38 To determine the severity of each LH area, a severity indicator based on the size and the number of nodules to produce a parameter on potential severity, as shown in Figure 5, has been described. 37 Increasing severity, as indicated by this model, is associated with increasing size and number of LH nodules and increasing amounts of inflammation, thickening, and loss of differentiation between the dermis and SC tissue. The insulin antibody load was also examined in individuals with varying severity of LH, and the antibody titer was associated with the severity of LH as defined in the model.…”
Section: Ultrasound Imaging Of Lipohypertrophymentioning
confidence: 76%
“…Hypoechogenic areas suggestive of necrotic tissue were also observed within the LH nodules in 30% of participants. 37 In addition, a recent cross-sectional study of adolescents and young adults (n = 95) with T1D found that participants with LH had significantly higher levels of TNFα, which is an inflammatory marker. 4 Studies suggest an average of 10 nodules per individual affected by LH, widely distributed but mainly located in the abdomen and thighs.…”
Section: Ultrasound Imaging Of Lipohypertrophymentioning
confidence: 99%
See 2 more Smart Citations
“…The echo signature for LD is described as well-circumscribed hyperechoic foci with defined borders or a nodular shape with a hypoechoic halo, heterogeneous in echotexture compared with surrounding tissue, associated with distortion of surrounding connective tissue in the absence of vascularity and absence of capsule. A relatively recent study confirmed that insulin-exposed tissue changes are heterogenous, and the authors provided a theoretical grading system for categorizing these changes (52,53).…”
Section: Figure 1 Grading Of Insulin-induced Subcutaneous Lipohypertr...mentioning
confidence: 89%